2019
DOI: 10.1021/acs.joc.9b01578
|View full text |Cite
|
Sign up to set email alerts
|

Azulichlorins and Benzocarbachlorins Derived Therefrom

Abstract: Acid-catalyzed condensation of azulidipyrrane aldehydes with a dihydrodipyrrin carbaldehyde afforded the first examples of azulichlorins. These macrocyclic products were isolated in a monoprotonated form, and the free bases proved to be somewhat unstable. The monocations were strongly diatropic, and proton NMR spectroscopy showed the internal C−H at ca. −2 ppm. Addition of TFA gave the related dications, but these exhibited significantly reduced aromatic ring currents. Reaction of an azulichlorin with tert-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The aromatic characters of heterocarbaporphyrins were assessed using nuclear independent chemical shift (NICS) calculations and anisotropy of induced current density (AICD) plots, methods we have previously applied to related porphyrinoid systems. NICS(0) calculations are commonly used to identify the aromatic characteristics of porphyrinoid systems, but the results can be misleading, as the effects of both the σ and π electrons are included. NICS zz calculations carried out 1 Å above the ring (NICS(1) zz ) emphasize contributions from the π system, and this method is a more reliable indicator of macrocyclic diatropicity.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The aromatic characters of heterocarbaporphyrins were assessed using nuclear independent chemical shift (NICS) calculations and anisotropy of induced current density (AICD) plots, methods we have previously applied to related porphyrinoid systems. NICS(0) calculations are commonly used to identify the aromatic characteristics of porphyrinoid systems, but the results can be misleading, as the effects of both the σ and π electrons are included. NICS zz calculations carried out 1 Å above the ring (NICS(1) zz ) emphasize contributions from the π system, and this method is a more reliable indicator of macrocyclic diatropicity.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The type i and j protons of the benzene ring are shifted downfield since they are a part of the global aromatic circuit, and the resonance values are comparable to those of an aromatic carbatriphyrin complex. 31,32 All of the proton resonances in compound 10 were shifted downfield in comparison to its phlorin analogue 7, supporting the presence of a diatropic ring current and also validating the aromatic nature of the B(III) complex of benzitriphyrin(2.1.1). Complex 10 showed a broad resonance at −2.56 ppm in 11 B NMR (Figure S5 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…It has been suggested that these transformations involve initial nucleophilic attack onto the azulene rings and that this triggers a Cope rearrangement, which leads to the observed benzocarbaporphyrins. Azulichlorins were recently shown to undergo similar ring contractions, providing access to a new class of benzocarbachlorins . It was much less clear that azulitriphyrins(1.2.1) would undergo transformations of this type as nucleophilic additions to this system appeared to give complex results.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the seven-membered ring is prone to nucleophilic attack and this facilitates oxidative ring contractions with peroxides under basic conditions to afford benzocarbaporphyrins 2 . The intriguing properties of azuliporphyrins have led to the preparation of other azulene-containing porphyrinoids, including azulisapphyrin 3 , azulicorrole 4 , azulichlorins 5 , dioxa-, dithia-, diselena- and ditellura-diazuliporphyrins, adj -diazuliporphyrins 6 , and related conjugated systems (Figure ). Although expanded azuliporphyrins have been investigated, the only example of a contracted azuliporphyrinoid is azulicorrole 4 .…”
Section: Introductionmentioning
confidence: 99%